1997
DOI: 10.1097/00000539-199701000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Acute Hypervolemic Hemodilution with Hydroxyethylstarch

Abstract: Acute normovolemic hemodilution (ANH) may help to reduce demand for homologous blood but requires extra time and apparatus. A more simple procedure is acute hypervolemic hemodilution (HHD), where hydroxyethylstarch is administered preoperatively without removal of blood. In a prospectively randomized study we compared ANH (preoperatively 15 mL/kg autologous blood removal and replacement with 15 mL/kg of hydroxyethylstarch with HHD (15 mL/kg of hydroxyethylstarch administered preoperatively) in 49 patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…With respect to hypervolaemic haemodilution (HHD), comparable data in the literature are very rare. Besides one clinical study on a small number of patients comparing HHD versus ANH [16], those data mainly refer to case reports [17,18]. The very few MM on HHD versus no-HHD published differ from each other in both mathematical description of the model itself [13,19] and the degree of hypervolaemia assumed [13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to hypervolaemic haemodilution (HHD), comparable data in the literature are very rare. Besides one clinical study on a small number of patients comparing HHD versus ANH [16], those data mainly refer to case reports [17,18]. The very few MM on HHD versus no-HHD published differ from each other in both mathematical description of the model itself [13,19] and the degree of hypervolaemia assumed [13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, ANH is sometimes accused of being a timeand equipment-consuming technique [3]. Instead of simultaneously exchanging the patient's blood versus a cell-free solution as seen in ANH, some studies used acute preoperative volume expansion without any blood removal and considered this technique hypervolemic hemodilution (HHD) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of simultaneously exchanging the patient's blood versus a cell-free solution as seen in ANH, some studies used acute preoperative volume expansion without any blood removal and considered this technique hypervolemic hemodilution (HHD) [4,5]. Based on those reports some authors even suggested replacing ANH with HHD, which they thought to be easier to handle [3]. So far, very little is known about the efficacy of HHD compared to ANH and further clarification is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na cirurgia de artroplastia de quadril sob anestesia geral com isofluorane, hemodiluição hipervolêmica com volume de 15ml/kg se mostrou uma técnica atrativa, com queda de custos, facilidade de uso, menor taxa de transfusão (43%x35%), quando comparada à hemodiluição normovolêmica aguda com sangramento acima de 1000 ml (Mielke et al, 1997), e com valores de hemodiluição normovolêmica aguda = 40% x hiperdiluição hipervolêmica = 20% (Saricaoglu et al, 2005).…”
Section: Hidroxietilamido (Hes)unclassified